2020
DOI: 10.4103/apjon.apjon_17_20
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Education Program on Nursing Knowledge and Attitude toward Pain Management

Abstract: Objective: Nurses have an integral role in pain assessment and management. Adequate knowledge and positive attitudes toward pain management are essential to provide high-quality nursing care for cancer pain. The purposes of this study are to evaluate nurses' knowledge and attitude toward cancer-related pain and to assess the effectiveness of a pain management education program on nurses' knowledge and attitude toward pain. Methods: A quantitative, experimental design wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
(57 reference statements)
1
8
1
1
Order By: Relevance
“…The present study revealed that more than two thirds of the studied nurses were female and married. This result disagrees with El-Aqoul et al (19) in their study reported that more than half of the studied nurses were male. While, this finding is congruent with Wang et al (6) in their study reported that majority of nurses were married.…”
Section: Discussioncontrasting
confidence: 95%
“…The present study revealed that more than two thirds of the studied nurses were female and married. This result disagrees with El-Aqoul et al (19) in their study reported that more than half of the studied nurses were male. While, this finding is congruent with Wang et al (6) in their study reported that majority of nurses were married.…”
Section: Discussioncontrasting
confidence: 95%
“…In relation to sex, in the present study it was found that (87.5%) were females and (12.5%) of them were males .This is in line with Musleh Band et al 2015 (60) , who reported that (87.3%) of the studied nurses were females and 12.7% were males. This is with disagreement with Sharour L 2018 (61) who report that 61.8 % were males and 47.3 %were females, and also rejected by El-AqoulA and et al A 2020 (62 ) , who reported that 60.3 % were males and 39.7% were females. Mersha A2020 (65) who reported that the majority (83.3%) of participants had a bachelor's degree in nursing.…”
Section: Table (2) Showed Percent Distribution Of Levels and Mean Sco...mentioning
confidence: 86%
“…Nurses have multidimensional and fundamental interventions in cancer pain management (El-Aqoul et al, 2020). These includes assessment of pain and continuous reassessment, managing pain using non-pharmacological and pharmacological approaches, teaching the patients and also their families about pain medication, assessing pain and the plan of treatment, and to be the patients' advocate assuring that patients have their own rights in regard to pain management (El-Aqoul et al, 2020). However, in order to achieve all of these interventions, positive attitudes and sufficient knowledge towards the management of pain are necessary (El-Aqoul et al, 2020).…”
Section: Nurses' Intervention In Promoting Self-management Of Cancer ...mentioning
confidence: 99%